Guidance for Methods Descriptions Used in Preclinical Imaging Papers - David Stout; Stuart S. Berr; Amy LeBlanc; Joseph D. Kalen; Dustin Osborne; Julie Price; Wynne Schiffer; Claudia Kuntner; Jonathan Wall (Molecular Imaging)
Preclinical molecular imaging is a rapidly growing field, where new imaging systems, methods, and biological findings are constantly being developed or discovered. Imaging systems and the associated software usually have multiple options for generating data, which is often overlooked but is essential when reporting the methods used to create and analyze data. Similarly, the ways in which animals are housed, handled, and treated to create physiologically based data must be well described in order that the findings be relevant, useful, and reproducible. There are frequently new developments for metabolic imaging methods. Thus, specific reporting requirements are difficult to establish; however, it remains essential to adequately report how the data have been collected, processed, and analyzed. To assist with future manuscript submissions, this article aims to provide guidelines of what details to report for several of the most common imaging modalities. Examples are provided in an attempt to give comprehensive, succinct descriptions of the essential items to report about the experimental process.